Penggunaan Media Digital dalam Pembelajaran Pendidikan Pancasila di Kelas VB SD Negeri 09 Kota Bengkulu - Nadila Rara Madaniati; Osa Juarsa; Yuli Amaliyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of digital media in Pancasila Education learning in class VB at SD Negeri 09 Kota Bengkulu. The research problem in this study is how digital media is used in Pancasila Education learning in class VB at SD Negeri 09 Kota Bengkulu, which is further elaborated into specific research questions, namely what types of digital media are used by the teacher and how the stages of using digital media are carried out, including planning, implementation, and evaluation of learning. This study uses a qualitative approach with a descriptive method. The research subject is the class VB teacher at SD Negeri 09 Kota Bengkulu. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted through several stages, namely data collection, data reduction, data presentation, and conclusion drawing and verification. The validity of the data was tested through triangulation, member checking, and reference materials. The results show that the digital media used include YouTube, Wordwall, and Kahoot!, which are used once to twice a week according to the learning materials. In the planning stage, the teacher considers the learning objectives, materials, students’ characteristics, and available facilities and infrastructure, then prepares the learning tools. In the implementation stage, digital media is used interactively through explanations and question-and-answer sessions between the teacher and students. In the evaluation stage, the teacher assesses the effectiveness of digital media use based on students’ engagement and understanding during the learning process. Overall, the use of digital media in Pancasila Education learning in class VB at SD Negeri 09 Kota Bengkulu has been implemented well through various types of media and learning stages, although it has not yet been supported by formal written policies. Keywords: Digital Media, Learning, Civics Education.